Under‐representation of avian studies in landscape genetics. (20th September 2017) - Kozakiewicz, Christopher P.; Carver, Scott; Burridge, Christopher P.
Abstract : Landscape genetics is a rapidly growing discipline that examines how heterogeneous landscapes and other environmental factors influence population genetic variation. We conducted a systematic review of the landscape genetic literature which demonstrates that birds are severely under‐represented relative to their species diversity and general publication prevalence. Most avian studies were on species that have relatively low dispersal ability, and we suggest that this reflects an assumed high vagility of birds that precludes spatial genetic variation relatable to landscape heterogeneity. However, spatial genetic variation exists in several bird species with very high dispersal ability, but this has not been considered in the context of landscape features. Genetic patterns may also relate to landscape due to breeding habitat selection and territorial behaviour, despite the fact that species may be able to move throughout different landscape elements with minimal movement costs. Habitat loss and fragmentation are continuing globally and are strongly related to declines in bird populations. Landscape genetic studies provide a means to understand, predict and mitigate the effects of anthropogenic landscape change on birds. This review promotes the need for landscape genetic studies of birds, such that a greater understanding of the drivers of their genetic structuring can be developed and generalizations can be made from landscape genetic studies that apply more broadly across taxa.